Az emberi erőforrás menedzsment egyes területeinek jelentősége Hajdú-Bihar és Szabolcs-Szatmár-Bereg megyékben - Gergely, Éva (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
Nowadays human resource management is of prior significance, since the human resource is the most important resource that determines the success of an organisation. Human resource management includes many activity areas of which the most important activities are the follows: employment analysis - planning - evaluation, human resource planning, labour supply, performance assessment, incentive, development of human resources, labour relations, labour safety, HRM information system. In the course of my examinations I wanted to find the answer how these functions are assessed by the employees of the organisations, which are considered as the most important. I executed my examinations in the county of Hajdú-Bihar and Szabolcs-Szatmár-Bereg. I applied surveys, and the questionnaires were processed by the SPSS 13 programme.